SADAR KEKERASAN GENDER BERBASIS ONLINE (KBGO): EDUKASI DIGITAL BAGI REMAJA SMP DI KOTA JAYAPURA - Abidjulu, Fitrine Christiane; Banurea, Rima Nusantriani; Lekka, Hendry Parinding; Waroy, Novita Syahbani; Waroy, Fatmawati Patiri (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2025)
Online gender-based violence (OGBV) poses a serious risk to teenagers, especially those with low digital literacy. Although teenagers are the most active internet users, many remain unaware of the threats posed by the digital space. This community service program aimed to raise awareness and educate junior high school students on GBV in the online sphere. Conducted on May 30, 2024, at SMP Negeri 11 Kota Jayapura, the program targeted 41 students (27 female and 14 male) aged 13–16 years, representing grades VII–IX. The activity was carried out in three stages: a pretest to assess initial knowledge, a 90-minute awareness session using customized SAFEnet materials delivered in Papuan dialect, and a posttest to measure learning outcomes. Data were collected through structured questionnaires, and results were analyzed quantitatively by comparing pretest and posttest responses. The findings showed a significant increase in student knowledge across all key OGBV topics. For example, awareness of the term OGBV rose from 3.7% to 100% among female students and from 0% to 100% among male students. These results indicate that targeted digital literacy programs can be highly effective in improving students’ understanding of online safety and gender-based violence. The activity also fostered critical awareness that the internet, while useful, is not always a safe space. This initiative is expected to empower teenagers to use digital platforms more wisely and safely while promoting respectful online interactions.